Synthesis and Characterization of Sorbitol Membraneless Alkaline Fuel Cell Catalysts for Cathode and Anode, Utilizing AgV2O5/C, AgMnO2/C, and PdCeO2/C Catalysts - Chaiburi, Chakkrapong; Chayboonchoo, Pintira (Trends in Sciences, 2024)
This study aimed to develop sorbitol fuel cell catalysts for cathode and anode fuels by synthesizing AgV2O5/C, AgMnO2/C, and PdCeO2/C catalysts. The physical characteristics of the catalysts were analyzed using SEM and EDS. The results showed that the prepared catalysts were small, lumpy, and densely clustered on the carbon surface with small particles. The electrochemical characteristics of the oxidation of alkaline fuels using sorbitol as fuel were investigated by assessing sorbitol concentration ratios of 0.1, 0.2, 0.3, 0.4 and 0.5 per 0.1 M alkaline KOH solution through cyclic voltammetry. The PdCeO2/C catalyst at a concentration of 0.1 M sorbitol solution exhibits the highest potential difference at the potential range of -0.5 to 0.5 V, resulting in a maximum current density of 0.2 mA/cm2. The AgV2O5/C and AgMnO2/C catalysts were tested in the reduction reaction, and the concentration ratios of sorbitol solution per 0.1 M alkaline KOH solution varied from 0.1 to 0.5 M. The results demonstrated a decrease in activity in the catalyst reduction reaction as the sorbitol solution concentration increased, indicating a potential correlation with enhanced oxidation resistance. HIGHLIGHTS In order to achieve the highest efficiency and suitability in an electric cell, it is essential for the AgV2O5/C and AgMnO2/C catalysts to possess excellent resistance to cathode oxidation The AgV2O5/C and AgMnO2/C catalysts function as cathode-side catalysts involved in reduction reactions. Consequently, it is imperative for these catalysts to exhibit exceptional resistance to oxidation at the cathode At a concentration of 0.1 M KOH solution, the PdCeO2/C catalyst exhibited a maximum oxidation current density of 0.2 mA/cm² GRAPHICAL ABSTRACT